Ergogenic demands of a 24 hour cycling event. Issue 3 (September 1984) - White, J. A.; Ward, C.; Nelson, H.
Abstract : The maximal aerobic performance (VO2 max) and energy costs of cycling at various power outputs and equivalent road speeds of a highly trained endurance cyclist (age 23.4 yrs, height 1.95 m, weight 73.1 kg), were measured in the laboratory on an eddy-current cycle ergometer, and the physiological responses related to determinations made during a 24 h cycling time trial event, using continuous ECG recording from which estimates of ergogenic demands were obtained. The cyclist covered a distance of 694 km during the event at an average speed of 28.9 km.h-1 which corresponded to an equivalent oxygen cost of 38.5 ml.kg-1 min-1 and represented approximately 55% of his VO2 max. During the event, the cyclist expended an estimated 82, 680 kJ of energy, of which approximately 44, 278 kJ (54%) were supplied by repeated feedings of liquids, solids and semi-solids and some 38, 402 kJ (46%) came from the stored energy reserves which resulted in a 1.19 kg loss of body weight during the event. The energy demands of the activity were more than three times greater than the highest recorded values of severe industrial work, and similar to the hourly rates of expenditure of shorter duration competitive events, but above the highest values reported over other extreme endurance events over the same period of time. The results thus represent near maximal levels of sustainable ergogenic effort by man over a complete 24 h cycle.